AB0394 Free light chains in sjögren's syndrome: correlations with eular scores, depression, and quality of life: a prospective cross-sectional study. (23rd January 2014) - Jülich, M.; Bojanow, A.-M.; Sehnert, B.; Voll, R. E.; Kollert, F.
Abstract : Background: Primary Sjögren's syndrome (pSS), a chronic and slowly progressive autoimmune disease, is characterised by lymphocytic infiltration of the exocrine glands characteristically leading to xerostomia and keratoconjunctivitis sicca[1 ]. Furthermore, the disease can cause severe organ manifestations like interstitial lung disease, cryoglobulinaemic vasculitis, and central or peripheral nervous system-involvement. Moreover, the risk for the development of malignant lymphoma is considerably enhanced[2 ]. Serum levels of immunoglobulin free light chains (FLC) are known to be increased in some autoimmune diseases[3, 4 ]. In pSS FLC levels are associated with extraglandular disease [5 ], whether there are correlations to other parameters of clinical manifestations, quality of life, depressive symptoms, and EULAR scores is yet unknown. Objectives: To investigate the correlation between FLC serum levels and disease activity as measured by EULAR scores, glandular symptoms, depressive symptoms, and quality of life (QoL) in pSS. Moreover, autoantibodies against Ro/SSA and La/SSB were analysed concerning their light chain distribution. Methods: Thirty-one patients with pSS and without history of lymphoma or evidence of paraproteinaemia were included in this prospective cross-sectional study. The assessment of disease activity was implemented by ESSDAI and ESSPRI. Depressive symptoms were documented with the Patient Health Questionnaire (PHQ-9) and QoL with the 12-Item Short Form Health Survey (SF-12). Light chain distribution of autoantibodies against Ro/SSA and La/SSB was analysed by ELISA. Results: We found a correlation between κFLC levels and disease activity as measured by the ESSDAI (r=0.646, p<0.001). κFLC levels correlated with β2-microglobulin concentrations (r=0.613, p<0.001). sIL2-R neither correlated with FLC levels (κ: p=0.500; λ: p=0.692) nor with the ESSDAI (p=0.130). The ESSPRI (p=0.438, p=0.792), PHQ-9 (p=0.233, p=0.183), and physical QoL (p=0.43, p=0.990) did not correlate with κ or λFLC levels. Conclusions: We found a correlation between κFLC levels and disease activity as measured by the ESSDAI (r=0.646, p<0.001). κFLC levels correlated with β2-microglobulin concentrations (r=0.613, p<0.001). sIL2-R neither correlated with FLC levels (κ: p=0.500; λ: p=0.692) nor with the ESSDAI (p=0.130). The ESSPRI (p=0.438, p=0.792), PHQ-9 (p=0.233, p=0.183), and physical QoL (p=0.43, p=0.990) did not correlate with κ or λFLC levels. References: Fox RI. Sjögren's syndrome. Lancet 2005;366:321-31. Johnsen SJ, Brun JG, Gøransson LG, et al. The risk of non-hodgkin lymphoma in primary sjögren's syndrome, a population-based study. Arthritis Care Res2012 published on 8 November 2012. doi:10.1002/acr.21887 Sølling K, Sølling J, Rømer FK. Free light chains of immunoglobulins in serum from patients with rheumatoid arthritis, sarcoidosis, chronic infections and pulmonary cancer. Acta Med Scand 1981;209:473-7. Urban S, Oppermann M, Reucher SW et al. Free light chains (FLC) of immunoglobulies as parameter resembling disease activity in autoimmune rheumatic diseases. Ann Rheum Dis 2004;63(Suppl 1):141. Gottenberg J, Aucouturier F, Goetz J, et al. Serum immunoglobulin free light chain assessment in rheumatoid arthritis and primary Sjogren's syndrome. Ann Rheum Dis 2007;66:23-7. Acknowledgements: The authors thank the patients and Stefanie Bartschat, Renate Helfesrieder, Joshua Henne, and Birgit Nettlenbusch for the excellent technical assistance. Disclosure of Interest: None Declared